ESTs identification and construction of normalized cDNA libraries of Miscanthus lutarioriparius across combinations of salt and drought stresses: ESTs of M. lutarioriparius under salt and drought - Liao, Jianfeng; Yi, Zili; Sun, Qian; Han, Yulai (Cellular and Molecular Biology, 2025)
Miscanthus lutarioriparius is a perennial C4 herb with high biomass production and is widely utilized as a non-food biobased material for bioproduction. This study successfully constructed two high-quality full-length normalized cDNA libraries from distinct salt-tolerant accessions of M. lutarioriparius under salt, drought, and combined salt-drought stress conditions. The study identified 420 high-quality Expressed Sequence Tags (ESTs) primarily associated with signal transduction mechanisms, post-translational modifications, energy production and transformation, as well as the synthesis, transport, and metabolism of amino acids, carbohydrates, and secondary metabolites. A total of 1370 Gene Ontology (GO) terms were obtained from two accessions, mainly related to cellular process, metabolic process, response to stimulus, biological regulation, biological regulation, cellular anatomical entity, binding, and catalytic activity. Five GO terms from the Biological Process Ontology consistently exhibited high P-values in both accessions, primarily associated with responses to exogenous substances and metabolic processes. The significant enrichment of genes associated with cellular components such as the chloroplast matrix, cytoplasm, and plastid matrix from the Cellular Component Ontology may explain the salt-drought tolerance mechanism of Miscanthus. This study is expected to deepen our understanding of the functional genes in Miscanthus plants and may provide a reference for screening salt and drought-resistance genes.